Analysis of potential of Napier grass, Vetiver and Equisetum plants for the treatment of domestic greywater using box-type constructed wetlands - Sijimol MR (IWA Publishing, 2021)
The management of wastewater generated as a byproduct of various human activities from agricultural, industrial, and domestic sectors is a matter of global concern today. Greywater is a class of wastewater generated from the domestic sector. Greywater management can be done effectively by treating greywater at the source itself. In this context, constructed wetlands (CWs) come handy with low-tech, environmental, and economic-friendly options. In the present study, box-type horizontal subsurface flow constructed wetlands were designed and the efficiency of Napier grass (Pennisetum purpureum), Vetiver (Vetiveria zizanioides), and Equisetum (Equisetum hyemale) were assessed in treating domestic greywater. There was a drastic significant increase in DO with 47.0% in Vetiver, 92.5% in Napier grass, and 97.2% in Equisetum. The average percent pollutant removal of some major parameters was 92.4% for turbidity, 92.7% for acidity, 81.3% for BOD, 91.0% for COD with Napier grass. In the case of Vetiver, the removal percent was 82.5% turbidity, 87.9% acidity, 81.8% BOD, and 92.9% COD. For Equisetum, the average pollutant removal efficiency varied with 94.6% turbidity, 91.4% acidity, 80.0% BOD, and 88.1%COD. The study thus proves the efficiency of all the three plants to be used in box-type constructed wetlands. HIGHLIGHTS Construction of box type constructed wetlands.; Constructed wetlands for the treatment of domestic greywater.; Analysis of the effectiveness of Napier grass, Equisetum, and Vetiver for the treatment of domestic greywater.; Reuse of treated greywater.; Application of box-type constructed wetlands in developing countries.;